MOTIVASI PEMAKAIAN CADAR BAGI MUSLIMAH: STUDI LIVING QUR’AN TENTANG PEMAHAMAN SURAH AL-AHZAB [33]: 59 DI KELURAHAN DENAI KECAMATAN MEDAN DENAI KOTA MEDAN - Triyana Lubis, Intan; Daulay, Maraimbang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the phenomenon of the use of the niqab among Muslim women as part of religious practices that have emerged in urban society. The primary focus of the study is on understanding Surah Al-Ahzab [33]: 59 and how this verse is interpreted and implemented in daily life by Muslim women in Denai Village, Medan Denai Subdistrict, Medan City. This phenomenon is worth studying due to the diversity of motivations underlying the wearing of the veil, whether theological, social, or personal. This study employs a qualitative approach using the “Living Qur’an” study method, which positions the Qur’an as a living text within the social practices of the community. Data were collected through in-depth interviews, participant observation, and documentation of informants who are Muslim women wearing the niqab in Denai Village. Data analysis was conducted using a descriptive-analytical approach, tracing the relationship between the understanding of religious texts and the reality of social practices. The results indicate that the motivations for wearing the niqab are not singular but diverse, encompassing religious impulses as a form of obedience to the Qur’an’s commands, efforts to preserve personal dignity, as well as the influence of the social environment and religious communities. Furthermore, it was found that the interpretation of Surah Al-Ahzab [33]: 59 tends to be understood textually by some informants, while others combine a contextual approach. The practice of wearing the veil in this context reflects the internalization of Qur’anic values that are alive within society. Thus, this study confirms that the phenomenon of the veil is a manifestation of the diverse and contextual dynamics of Qur’anic interpretation in the lives of modern Muslim women.